Foreign ministries : managing diplomatic networks and optimizing value - Rana, Kishan S. (DiploFoundation MsidaMT, 2007)
Discusses the challenges faced by foreign ministries from all over the world, viz, its character as an organisation and the significance of organisational culture in understanding its character.